2012
DOI: 10.1002/ar.22478
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Gyrification in Cynomolgus Monkeys: A Concept of Developmental Stages of Gyrification

Abstract: Our article summarizes a series of studies about fetal gyrification and its relation to cerebral growth in cynomolgus monkeys. Based on the cerebral growth (i.e., brain weight, cerebral volume, and frontooccipital length of the cerebral hemisphere) and the developmental pattern of gyrification in each sulcus of cynomolgus monkeys, we divided the gyrification process into four stages: Stage 1. Demarcation of cerebral lobes and limbic gyri; Stage 2. Demarcation of neocortical gyri; Stage 3. Emergence of secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 57 publications
(98 reference statements)
4
46
0
Order By: Relevance
“…3D reconstructions of fetal human brains from Barnette et al (2009). Figure follows Sawada et al (2012b). …”
Section: The Chronology Of Neocortical Folding During Development supporting
confidence: 52%
See 1 more Smart Citation
“…3D reconstructions of fetal human brains from Barnette et al (2009). Figure follows Sawada et al (2012b). …”
Section: The Chronology Of Neocortical Folding During Development supporting
confidence: 52%
“…The correlative increase in cerebral volume and gyrification during this stage, including a dramatic increase in gyri in the occipital region, may in fact constitute the formation of a characteristic pattern of gyrencephaly common to all gyrencephalic primates. Work in Old World monkeys has shown that all neocortical gyri, with the exception of the superior temporal gyrus, emerge during Stage 1 and that both the chronology of emergence and rostrocaudal distribution of gyri are homologous in monkeys and humans (Zilles et al, 1988; Rilling and Insel, 1999; Sawada et al, 2012a,b). There is, despite this broad conservation, a delayed emergence of the parietoccipital gyri (e.g., cuneus, angular gyrus, supramarginal gyrus) in humans compared to monkeys, which, because these gyri are associated with Wernicke's area in humans but dorsal extrastriate cortex in monkeys (Sawada et al, 2012a,b), may indicate that heterochronic changes in gyri emergence reflect species-specific adaptations in particular cortical regions.…”
Section: The Chronology Of Neocortical Folding During Development mentioning
confidence: 99%
“…Restricting phenotypic variance into modules also allows systems to evolve patterns of correlation that facilitate future alteration of evolutionary traits through the convergence of genetic and functional modules (Cheverud 1996;Wagner 1996). The similarity of variation structure in genetic and phenotypic matrices thus illustrates the selective grouping of traits into related units in these two domains, providing a ready framework for future adaptive morphological change and an evolutionarily beneficial situation of increased morphological integration for traits that need to be functionally compatible with one another in an organism's life.The similarity in matrix variation structure between the anatomical location of the sulci and the day on which the sulcus first emerges during development parallels ontogenetic findings that the brain typically develops the primary and most deep-set folds first during development, with secondary folds developing next, and superficial wrinkles and projections off of the primary folds developing last (Huang et al 2009;Sawada et al 2012). The bulk of the primary folds are located toward the central region of the brain (lf, sts, cs), followed by the back of the brain (lu, ips), and finally the frontal folds (ps, spcd, iar).…”
mentioning
confidence: 81%
“…Based on embryonic day of emergence of each landmark sulci. Created from data presented in Sawada et al (2012).…”
Section: Extended Explanation Of Covariate Screeningmentioning
confidence: 99%
See 1 more Smart Citation